Teen Titans go! : to the library! - Aureliani, Franco (Teen Titans go!, 2023)
When a villain unleashes chaos at the library, the Teen Titans get scattered into the library books and must first figure out what happened, then find each other, then find the real Jump City--all while punching, posing and reading.